Controls on Larsen C Ice Shelf Retreat From a 60‐Year Satellite Data Record. Issue 3 (1st March 2022) - Wang, Shujie; Liu, Hongxing; Jezek, Kenneth; Alley, Richard B.; Wang, Lei; Alexander, Patrick; Huang, Yan
Abstract: Rapid retreat of the Larsen A and B ice shelves has provided important clues about the ice shelf destabilization processes. The Larsen C Ice Shelf, the largest remaining ice shelf on the Antarctic Peninsula, may also be vulnerable to future collapse in a warming climate. Here, we utilize multisource satellite images collected over 1963–2020 to derive multidecadal time series of ice front, flow velocities, and critical rift features over Larsen C, with the aim of understanding the controls on its retreat. We complement these observations with modeling experiments using the Ice‐sheet and Sea‐level System Model to examine how front geometry conditions and mechanical weakening due to rifts affect ice shelf dynamics. Over the past six decades, Larsen C lost over 20% of its area, dominated by rift‐induced tabular iceberg calving. The Bawden Ice Rise and Gipps Ice Rise are critical areas for rift formation, through their impact on the longitudinal deviatoric stress field. Mechanical weakening around Gipps Ice Rise is found to be an important control on localized flow acceleration and the propagation of two rifts that caused a major calving event in 2017. Capturing the time‐varying effects of rifts on ice rigidity in ice shelf models is essential for making realistic predictions of ice shelf flow dynamics and instability. In the context of the Larsen A and Larsen B collapses, we infer a chronology of destabilization processes for embayment‐confined ice shelves, which provides a useful framework for understanding the historical and future destabilization of Antarctic ice shelves. Plain Language Summary: The Antarctic Ice Sheet is the largest source of uncertainty in projecting future sea‐level rise. This is due to our limited understanding of drivers and mechanisms triggering tipping points in ice‐sheet instability, and knowledge gaps regarding the retreat and disintegration of ice shelves. Understanding processes leading to ice shelf destabilization is critical to improving estimates of future Antarctic mass loss because of their important role in stabilizing ice flow. We studied Larsen C Ice Shelf changes using satellite data collected over 1963–2020, and conducted modeling experiments to elucidate the observed linkages between front retreat, flow acceleration, and rifts. We find the development of rifts near ice rises to be an important control on Larsen C front calving and flow acceleration in the past six decades. Rifts can affect each other by causing mechanical weakening and modifying stress fields. To predict future dynamical changes, it is necessary to account for this feedback and capture how ice rigidity changes over time in response to rift growth. If Larsen C retreats to the extent that the compressive arch ceases to exist, it will resemble the precollapsed Larsen B ice shelf, producing widespread flow accelerations in response to the backstress loss from ice rises. Key Points: Multidecadal satellite images and ice shelf modeling experiments were used to examine dynamic changes of Larsen C during 1963–2020 Rift development near ice rises is an important control on ice shelf retreat and flow acceleration before the compressive arch is reached Capturing the time‐varying effects of rifts on ice rigidity is needed to make realistic simulations of future ice shelf change